Estimation of soil shear modulus softening during strong ground shaking using ground surface and downhole acceleration recordings. - Davis, R.O.
An algorithm for estimating the average shear modulus for a soil site containing a downhole accelerometer array is described. For distant or weak earthquakes, the usual procedure for estimating shear modulus is to perform time series correlation of two downhole records. The vertical distance between instruments divided by the peak correlation lag time gives the average shear wave velocity. The shear modulus follows easily. This method is not applicable for stronger earthquakes where non-linear softening effects lead to progressively slower shear wave velocities. The method presented here overcomes the softening effect by compressing the time scale of the upper acceleration record. Time compression is accomplished in such a way that the peak correlation of the two records is maximized. The algorithm steps through the records, maximizing the correlation peak by adjusting the time scale within an active time interval. The resulting compressed upper record can be interpreted as the ground motion that would have occured had softening not taken place. The summation of the various time scale adjustments shows both the amount of softening and the time at which it occured.
Keywords: Downhole arrays; Shear modulus; Shear wave velocity; Softening; Cross correlation